Emission Reduction Policy for Construction Supply Chain with Mix Financing and Cap-and-trade. Issue 6 (March 2020) - Jiang, Wen; Zhang, Li; Liu, Menglin
Abstract: Under the cap-and-trade and the incentive of emission reduction bonus, we investigated a two-stage construction supply chain consisting of a subcontractor with capital constraints and a general contractor. Firstly, this paper constructed a decision model of emission reduction considering both internal financing and external financing (i.e. mix financing). Secondly, the optimal decisions and maximum profit of both parties are obtained. In addition, this study also showed that the total amount of emission reduction of the general contractor increases in carbon trading price; the total amount of emission reduction of the subcontractor increases in carbon trading price and decreases in external financing interest rate; the optimal proportion of internal financing increases in internal financing interest rate while decreases in external financing interest rate.